Bionanocomposites for Packaging Applications (Springer International Publishing, 2018)
This book presents a unified overview of eco-friendly bionanocomposites on the basis of characterization, design, manufacture, and application. It also explores replacing conventional materials with bionanocomposites with a focus on their use in packaging applications. In addition, the book broadens readers' insights by providing illustrations and tables summarizing the latest research on the packaging applications of different bionanocomposites. By offering a detailed account of this field of research and describing real-world applications, it enables researchers, scientists, and professionals in industry to develop a more informed understanding of the need for bionanocomposites in the development of green, biodegradable, and sustainable packaging applications.